(untitled) (Salud, Arte y Cuidado, 2020)
The objective of this research was to analyze the clinical characteristics of the vascular accesses of patients in the Lara II Dialysis Unit hemodialysis program. The study is descriptive in the field, with a quantitative approach, with a non-experimental design and a cross-sectional section. The Population constituted by 87 patients who attend three times a week. The technique is the survey and the instrument is a questionnaire designed by the researchers, consisting of 12 questions related to the type of vascular access, clinical characteristics of the temporary and definitive vascular access of the patients in the hemodialysis program, applied with prior informed consent, the results were Type of vascular access 66% have autologous vascular access and 24% have a catheter; the location of the vascular catheter 95% in the right subclavian vein and 5% in the left femoral vein and the types of fistulas 65% cephalic humerus, 30%, basilichumerus 5% cephalic radius; Fistula patients take 77% antiaggregants and 5% anticoagulants and 90% of catheter patients take Antiaggregants and do not take Anticoagulants; Catheter Complications stand out 76% have Infections, while 10% have Lymph Drainage and Dysfunction and 100% do not have Hematomas, Edema or Cuff Extrusion; While the Complications of the fistulas were 35% presented aneurysm, 6% infection, 8% edema and 3% thrombosis, 100% did not present neither theft nor hematoma; the frequent episodes of patients with fistula in the hemodialysis program are 61% delayed hemostasis time, 24% present hypotension, 9% insufficient flow, 5% attenuated trhill. It is concluded that it is necessary to improve the care of vascular access, with this, a reduction in complications can be achieved, greater longevity of the venous access, an increase in the quality of life of patients and a reduction in the cost induced by this problem.